2018
DOI: 10.1021/acs.jmedchem.8b00035
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Discovery and Characterization of Novel Ebola Virus Inhibitors

Abstract: The Ebola virus (EBOV) causes severe human infection that lacks effective treatment. A recent screen identified a series of compounds that block EBOV-like particle entry into human cells. Using data from this screen, quantitative structure-activity relationship models were built and employed for virtual screening of a ∼17 million compound library. Experimental testing of 102 hits yielded 14 compounds with IC values under 10 μM, including several sub-micromolar inhibitors, and more than 10-fold selectivity agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 62 publications
(130 reference statements)
0
23
0
1
Order By: Relevance
“…Tetrandrine, also known as Han‐Fang‐Ji‐Jia‐Su in Chinese, is a natural product belongs to the bis‐benzylisoquinoline alkaloid family that was originally isolated and purified from the roots of the traditional Chinese medicinal herb Stephania tetrandra S. Moore of the Menispermaceae family (see Figure 1). [ 37–40 ] Numerous investigations have demonstrated that this natural compound possesses a very broad‐spectrum of distinct pharmacological activities, including anticancer, [ 41 ] anti‐inflammatory, [ 42 ] anti‐nociceptive, [ 43,44 ] anti‐fibrotic, [ 45 ] anti‐depressant, [ 46 ] anti‐rheumatoid arthritis, [ 47,48 ] anti‐adipogenic, [ 49 ] anti‐microbial, [ 50,51 ] neuroprotective [ 52 ] and memory‐improving activities. [ 53,54 ]…”
Section: Introductionmentioning
confidence: 99%
“…Tetrandrine, also known as Han‐Fang‐Ji‐Jia‐Su in Chinese, is a natural product belongs to the bis‐benzylisoquinoline alkaloid family that was originally isolated and purified from the roots of the traditional Chinese medicinal herb Stephania tetrandra S. Moore of the Menispermaceae family (see Figure 1). [ 37–40 ] Numerous investigations have demonstrated that this natural compound possesses a very broad‐spectrum of distinct pharmacological activities, including anticancer, [ 41 ] anti‐inflammatory, [ 42 ] anti‐nociceptive, [ 43,44 ] anti‐fibrotic, [ 45 ] anti‐depressant, [ 46 ] anti‐rheumatoid arthritis, [ 47,48 ] anti‐adipogenic, [ 49 ] anti‐microbial, [ 50,51 ] neuroprotective [ 52 ] and memory‐improving activities. [ 53,54 ]…”
Section: Introductionmentioning
confidence: 99%
“…Some of these inhibitors are shown in Figure . Other studies include the identification of coumarin‐based antihistamine‐like molecules, benzoquinoline compounds (SW456 compound reported to be the most potent compound in the infectious EBOV assay, IC 50 = 0.5 μM), ellagic acid (IC 50 = 1.4 μM), and vindesine (IC 50 = 0.34 μM), that proved to have potential EBOV inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…The following metrics were computed and assessed by nested cross-validation: balanced accuracy (BA), mean misclassification error (MMCE), sensitivity (true positive rate (TPR)), specificity (true negative rate (TNR)), positive predictive value (PPV), and Area Under the Receiver Operating Characteristics Curve (AUC) with their widely known definitions and equations [121,122]. We were interested in predicting whether a particular substance may induce DILI; therefore, we focused on increasing the balanced accuracy, as well as PPV.…”
Section: Performance Evaluationmentioning
confidence: 99%